Industry 4.0 technologies and their applications in fighting COVID-19 pandemic using deep learning techniques. (June 2022) - Ahmad, Muhammad; Sadiq, Saima; Eshmawi, Ala' Abdulmajid; Alluhaidan, Ala Saleh; Umer, Muhammad; Ullah, Saleem; Nappi, Michele
Abstract: The disease known as COVID-19 has turned into a pandemic and spread all over the world. The fourth industrial revolution known as Industry 4.0 includes digitization, the Internet of Things, and artificial intelligence. Industry 4.0 has the potential to fulfil customized requirements during the COVID-19 emergency crises. The development of a prediction framework can help health authorities to react appropriately and rapidly. Clinical imaging like X-rays and computed tomography (CT) can play a significant part in the early diagnosis of COVID-19 patients that will help with appropriate treatment. The X-ray images could help in developing an automated system for the rapid identification of COVID-19 patients. This study makes use of a deep convolutional neural network (CNN) to extract significant features and discriminate X-ray images of infected patients from non-infected ones. Multiple image processing techniques are used to extract a region of interest (ROI) from the entire X-ray image. The ImageDataGenerator class is used to overcome the small dataset size and generate ten thousand augmented images. The performance of the proposed approach has been compared with state-of-the-art VGG16, AlexNet, and InceptionV3 models. Results demonstrate that the proposed CNN model outperforms other baseline models with high accuracy values: 97.68% for two classes, 89.85% for three classes, and 84.76% for four classes. This system allows COVID-19 patients to be processed by an automated screening system with minimal human contact. Graphical abstract: Image 1 Highlights: An improved convolutional neural network (CNN) model has been proposed for the detection of COVID-19 disease. A framework consisting of Industry 4.0 techniques is proposed to control the COVID-19 outbreak. Multiple image processing techniques are used for the edges detection and segmentation of the region of interest.